Pewarisan Objek Tanah Hak Milik Menurut Hukum Adat - Akmal Ricko Fery Anantha; Dominikus Rato; Dyah Octhorina Susanti (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2023)
Indigenous peoples control customary land for generations with inheritance regulated in customary inheritance law. Customary land in question has not been attached with land rights. The results of research using normative juridical methods with statutory approaches, conceptual approaches, and historical approaches provide an explanation thatinheritance related to the provisions regardinginherited assets that are transferred to control and ownership from heirs to heirs based on customary law rules, which have binding legal force for indigenous peoples. Land ownership rights are objects of inheritance which are material tangible assetsfirst and foremost. The process of inheriting land ownership rights to heirs based on customary inheritance law is carried out deliberation and kinship on the principle of mutual cooperation, running in harmony, peace and harmonycontains cultural values ​​and is recognized by the state. Furthermore, to guarantee legal certainty, legally, land registration is carried out on ownership rights to land as objects of inheritance. Keywords: Land Property Rights, Objects of Inheritance, Customary Inheritance Law.